Use of hospital services by age and comorbidity after an index heart failure admission in England: an observational study. Issue 6 (9th June 2016) - Bottle, Alex; Goudie, Rosalind; Bell, Derek; Aylin, Paul; Cowie, Martin R
Abstract : Objectives: To describe hospital inpatient, emergency department (ED) and outpatient department (OPD) activity for patients in the year following their first emergency admission for heart failure (HF). To assess the proportion receiving specialist assessment within 2 weeks of hospital discharge, as now recommended by guidelines. Design: Observational study of national administrative data. Setting: All acute NHS hospitals in England. Participants: 82 241 patients with an index emergency admission between April 2009 and March 2011 with a primary diagnosis of HF. Main outcome measures: Cardiology OPD appointment within 2 weeks and within a year of discharge from the index admission; emergency department (ED) and inpatient use within a year. Results: 15.1% died during the admission. Of the 69 848 survivors, 19.7% were readmitted within 30 days and half within a year, the majority for non-HF diagnoses. 6.7% returned to the ED within a week of discharge, of whom the majority (77.6%) were admitted. The two most common OPD specialties during the year were cardiology (24.7% of the total appointments) and anticoagulant services (12.5%). Although half of all patients had a cardiology appointment within a year, the proportion within the recommended 2 weeks of discharge was just 6.8% overall and varied by age, from 2.4% in those aged 90+ to 19.6% in those aged 18–45 (p<0.0001); appointments in other specialties made up only some of the shortfall. More comorbidity at any age was associated with higher rates of cardiology OPD follow-up. Conclusions: Patients with HF are high users of hospital services. Postdischarge cardiology OPD follow-up rates fell well below current National Institute for Health and Care Excellence guidelines, particularly for the elderly and those with less comorbidity.